Models of Sexual Assault Laws and Evidentiary Matters - Selman Dursun; Ali Emrah Bozbayındır (Ceza Hukuku ve Kriminoloji Dergisi)
One of the most important topics of discussion in criminal law in recent years has been the changes in understanding regarding sexual offenses and their related concepts. Following the acceptance that the legal value protected under sexual offences is individual rather than social, fundamental differences have occurred in the approaches and concepts. The current stage of this development involves a search for different models for this offense, particularly with regard to defining the offense of sexual assault. The traditional coercion-based model has come under various criticisms over time, with the so-called consent models having become a current issue. In addition to the coercion-based model, this study analyzes the consent-based models as affirmative and negative consent models of will and examines their implications for the law of evidence. The study briefly mentions French, Italian, Spanish, and German codes as examples of different models. Lastly, the study evaluates the regulation of sexual assault under Turkish law based on the abovementioned models. Regarding its historical development prior to the reform of the Penal Code in 2005, Turkish law adopted the coercion-based model. The article also discusses the post-new code discussions in detail.